Globalization Impact on Small and Medium Enterprise: Tanzania Case - Baraka Aligaesha; 박병주; 장병윤 (The International Journal of Internet, Broadcasting and Communication, 2019)
We are looking the impact associated with globalization in favor of small and medium enterprises (SMEs) growth and how helped to reduce the obstacle facing SMEs growth. We used empirical analysis in order to examine the relationship underlying the globalization and its impact to SME growth. We employed primarily data from Tanzania SMEs. Further we seeks to explain the negative notion that has been created that globalization is not friendly to SME growths. We employed primary data from Tanzania SMEs. The partial least squares (PLS) was used for analysis. The conclusion has indicated that globalization has a relationship with SMEs growth and has contributed to the reduction of obstacles that inhibit SMEs growth. However study confirmed controversial result on part of availability of managers and manpower with global perspectives to influence SMEs growth. The test accepted that globalization has influenced availability of managers with global perspectives but reject the availability of these managers influences the SMEs growth The results give a clear outlook to help policy maker in policy review process, formulate base for extensive study on issues for manager perspectives and draw intervention.
Keywords: Globalization; SMEs growth; PLS; empirical analysis; manager